Vortex Dynamics and Optical Vortices - Perez-de-Tejada, Hector (IntechOpen, 2017)
The contents of the book cover a wide variety of topics related to the analysis of the dynamics of vortices and describe the results of experiments, computational modeling and their interpretation. The book contains 13 chapters reaching areas of physics in vortex dynamics and optical vortices including vortices in superfluid atomic gases, vortex laser beams, vortex-antivortex in ferromagnetic hybrids, and optical vortices illumination in chiral nanostructures. Also, discussions are presented on particle motion in vortex flows, on the simulation of vortex-dominated flows, on vortices in saturable media, on achromatic vortices, and on ultraviolet vortices. Fractal light vortices, coherent vortex beams, together with vortices in electric dipole radiation, and spin wave dynamics in magnetic vortices are examined as well.